IMPLEMENTASI MEDIA PEMBELAJARAN SISILABAR TERHADAP HASIL BELAJAR SISWA KELAS VII DI SMP SUSILA KOTING - Sisilia Densiana; Tanti Diyah Rahmawati; Magdalena Dhema (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2023)
Learning media is very useful in the teaching and learning process so that the achievement of learning objectives. Sisilabar media si one of the learning media tjat helps students understand the operational material for addition and reducing the form of algebra. This study aims to find out how the implementation of sisilabar learning media on student the learning outcomes of class VII at Susila Koting junior high school. The typr of research used is descriptive qualitative. The technique thet is taken in data is tests and documentation. The result in this study show positive results after the implementation of sisilabar media. This can be proven by the result pretest and posttest of student. This average pretest student score is 46.3 while posttest average result are 81.7 and tha percentage of completeness of student pretest result reaches 12.5% while the posttest reaches 87.5%. So it can be concluded that the learning in the operation material for addition and reducing algebra.